الجريدة الرسمية العدد 38 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء : قرار رقم 2435 لسنة 2024 -- قرار رقم 2436 لسنة 2024 -- قرار رقم 2437 لسنة 2024 -- قرار رقم 2438 لسنة 2024 -- قرار رقم 2439 لسنة 2024 -- قرار رقم 2703 لسنة 2024 -- قرار رقم 2704 لسنة 2024 -- قرار رقم 2890 لسنة 2024 --